2014
DOI: 10.1681/asn.2013040435
|View full text |Cite
|
Sign up to set email alerts
|

BP, Cardiovascular Disease, and Death in the Folic Acid for Vascular Outcome Reduction in Transplantation Trial

Abstract: The optimal BP level in kidney transplant recipients remains uncertain. This post hoc analysis of the Folic Acid for Vascular Outcome Reduction in Transplantation (FAVORIT) trial cohort assessed associations of BP with a pooled cardiovascular disease (CVD) outcome and with all-cause mortality. In 3474 prevalent kidney transplant patients, mean age was 5269 years, 63% were men, 76% were white, 20% had a history of CVD, 40% had a history of diabetes mellitus, and the median time since transplant was 4.1 years (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 41 publications
2
30
1
Order By: Relevance
“…KDIGO, for example, grades its evidence for 130/80 mm Hg as 2C (weak recommendation with a low quality of evidence). A post hoc analysis on the Folic Acid for Vascular Outcome Reduction in Transplantation (FAVORIT) trial, which assessed the association of BP with pooled cardiovascular disease outcomes and all‐cause mortality in the original cohort, has shed some light on the subject and confirmed that higher levels of systolic BP are independently associated with higher risk of cardiovascular disease and all‐cause mortality without having a lower threshold below which risk also rises (the same could not be said for diastolic BP) …”
Section: Discussionmentioning
confidence: 99%
“…KDIGO, for example, grades its evidence for 130/80 mm Hg as 2C (weak recommendation with a low quality of evidence). A post hoc analysis on the Folic Acid for Vascular Outcome Reduction in Transplantation (FAVORIT) trial, which assessed the association of BP with pooled cardiovascular disease outcomes and all‐cause mortality in the original cohort, has shed some light on the subject and confirmed that higher levels of systolic BP are independently associated with higher risk of cardiovascular disease and all‐cause mortality without having a lower threshold below which risk also rises (the same could not be said for diastolic BP) …”
Section: Discussionmentioning
confidence: 99%
“…The paradox of reverse epidemiology is acknowledged in patients with ESRD on dialysis where J‐shaped (rather than linear) relationships are seen between blood pressure (BP) , cholesterol and body mass index and mortality risk. Following successful transplantation patients with ESRD have more conventional relationships between CV risk factors and outcome, as illustrated recently by post hoc analysis of the folic acid for Vascular Outcome Reduction in Transplantation trial , where there was a linear relationship between increasing systolic BP and mortality. Although more conventional relationships between CVD and risk factors evolve post‐transplantation, legacy of time spent on dialysis remains.…”
Section: Clinical Aspects Of Cvd In Kidney Transplantationmentioning
confidence: 99%
“…In conclusion, we have demonstrated within a large, multiethnic cohort of long-term, stable KTRs [8][9][10] that shortened T50 and lower serum fetuin-A concentrations, ostensible promoters of vascular calcification [1-4, 35, 36] were associated with greater risk for CVD events, and this relationship persisted after adjustment for major, established CVD risk factors, measures of kidney function and damage, and KTR clinical and demographic characteristics [16,17,19,20,24]. Future controlled studies of interventions [1,3,26,38] that could prolong T50 in KTRs, and other CKD patient populations, and the possible impact of such T50 prolongation on validated noninvasive measures of vascular calcification [43], and ultimately, clinical CVD outcomes [8], may be warranted.…”
Section: Resultsmentioning
confidence: 99%
“…Baseline blood pressure was the average of 2 measurements and hypertension [19] was defined by a systolic blood pressure ≄140 mm Hg, a diastolic ≄90 mm Hg or antihypertensive medication use at study enrollment. Diabetes was defined by the use of insulin or oral hypoglycemic medications or patient history.…”
Section: Other Measurementsmentioning
confidence: 99%